Progress and Analysis of Research on Phosphorus Collectors and their Interaction Mechanisms - Wenda GUO; Haolong LU; Yuanting JIANG; Zhenyue ZHANG; Meng HU; Ruan CHI (Kuangchan zonghe liyong)
This is an article in the field of mineral processing engineering.The phosphate ore is a non-renewable strategic non-metallic mineral, which plays a crucial role in social and economic development and technological progress. Flotation is the main way of phosphate ore beneficiation, and the collectors are at the core of phosphate ore flotation, which plays a decisive role in the resource recovery rate of phosphate ore. Based on the discussion the characteristics and utilization status of phosphate ore resources in China, this article systematically classifies the currently used phosphate ore collectors, provides typical examples of various collectors, and analyzes the characteristics, existing problems, and future development directions of various collectors. In addition, the current research status of the mechanism of the action of phosphorus selective collectors is summarized from two aspects: the adsorption mechanism of phosphorus selective collectors on mineral surfaces and the separation mechanism of flotation processes. This will provide useful references for the development of phosphorus ore flotation collectors and basic research of phosphorus ore flotation.